Impact, added value and relevance of an accreditation process on quality assurance in architectural higher education - Acevedo De los Ríos, Alejandra (2022)
The study examines the impact, added value and relevance of accreditation as a way of assuring quality at an institution of higher learning in the field of architecture. The qualitative impact of accreditation was examined through a survey presented to students, teachers and employers. A quantitative assessment was carried out by reviewing academic indicators, such as pass rate or weighted average per year, before and after the accreditation processes. The study examined a private institution of higher education in Peru; however, the methodology and results may be relevant to future studies of schools in developing countries with similar characteristics.